Cadmium Oxide:Titanium Dioxide Composite Based Photosensitive Diode - Karabulut, Abdulkerim; Dere, A.; Al-Sehemi, Abdullah G.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Springer, 2018)
Cadmium oxide:titanium dioxide (CdO:TiO2) composite thin films with various ratios of CdO contents were prepared on p-type silicon semiconductor substrates by the sol-gel spin coating method. Al/CdO:TiO2/p-Si/Al heterojunction devices exhibited optoelectronic device behavior due to their photocurrent under solar light illuminations. The photoresponse behavior of the diodes is controlled by changing the molar ratio of CdO to TiO2. The fabricated CdO:TiO2 (2:1) based device exhibited the highest photoresponse of about 7.5 x 10(3). The interface properties of the devices are changed with the molar ratio of CdO:TiO2. The obtained results suggest that CdO:TiO2 composite film/p-type Si structure can be used in optoelectronic applications.
Keywords: Electrical properties; photodiode; CdO:TiO2 composite; illumination effect; interfacial layer